RETRACTED: Effect of minimally invasive versus open surgery in hepatectomy on postoperative wound complications in patients with hepatocellular carcinoma: A meta‐analysis - Zhang, Junli; Shi, Meiping; Ding, Wan; Duan, Mingda; Dai, Ziqing; Chen, Yu (International wound journal, 2023)
In a meta‐analysis, we assessed the impact of different surgical approaches on the outcome of hepatectomy with hepatocellular carcinoma. Four databases, including PubMed, Embase, Cochrane Library, and the Web of Science, have been critically reviewed through the full literature through June 2023. Eleven related trials were examined once they had met the trial's classification and exclusion criteria, as well as the assessment of the quality. A random effects approach was applied to analysis of operative organ infections, and a fixed‐effect model was applied to determine the 95% CI and OR. Analysis of the data was done with RevMan 5.3. Our findings indicated that patients undergoing minimally invasive liver cancer surgery had significantly lower risks of surgical organ infection (OR, 0.35; 95% CI, 0.16–0.77; p = 0.009) and wound infection (OR, 0.19; 95% CI, 0.13–0.28; p < 0.001) compared to those undergoing open surgery. There was no heterogeneity observed between the two groups ( I 2 = 0) in wound infection. Nevertheless, because of the limited number of randomised controlled trials in this meta‐analysis, care should be taken and carefully considered in the treatment of these values. Further high‐quality studies involving a large number of samples are needed to validate and reinforce the results.